The form of eufemism in Jawa Pos newspaper column in 2023 - Anis Ayu Ashari (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Euphemisms are euphemism which are a figure of speech or an expression that is used to refine words, phrases, sentences that are harsh or taboo according to the context that follows them to protect the feelings of others. This study aims to: describe the form of euphemism and the function of using euphemisms. The focus of this research is (1) the form of using euphemisms in the Jawa Pos newspaper in 2023. The research is a qualitative research. The data used in this research are words, phrases, clauses, and sentences that contain euphemisms. Data was obtained by data collection techniques, namely reading and recording using the euphemism data table instrument. Data analysis techniques with data grouping, data couding, data interpretation, and data description. The results of this research are: (1) Several forms of euphemism are found, namely the use of initials and acronym abbreviations, the use borrowed words, the use of foreign terms, the use of metaphors, and the use of periphrases. Keywords: euphemisms, newspaper, and forms of euphemisms